IMPORTANCE OF PREOPERATIVE RADIOLOGICAL PLANNING IN THE REHABILITATION OF PATIENTS WITH ENDOPROSTHETIC KNEE ARTHROPLASTY - CASE STUDY - Liliana SAVIN; Victor GRIGORESCU; Teodor ZLATE; Marius NECULĂEȘ; Dan MIHĂILESCU; Carmen GRIEROSU; Paul BOTEZ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Introduction: The purpose of endoprosthetic knee arthroplasty is to restore joint function; this objective can be attained by positioning correctly the prosthetic elements both in frontal (varus-valgus) and in rotational plane. The new radiological planning protocol introduced since October 2014 in the Orthopaedics Clinic of the Rehabilitation Hospital manages to cover the entire preoperative assessment of frontal and rotational deformities. Case study: The 58-years-old female patient with bilateral gonarthrosis has benefited - in February 2013 from endoprosthetic arthroplasty for the left knee and in April 2015 for the right knee. The two joints were approached differently, it terms of both preoperative and intraoperative imaging protocol and postoperative rehabilitation program. Findings: The radiological control highlights the correct placement of the prosthesis in frontal and rotational plane, the absence of joint instability during right knee flexion and extension and a discrete misplacement in varus, an internal femoral malrotation of 50 and equal external laxity of the gap in flexion for left knee.